Isolation, cultivation, quantification of cellular carotenoids and identification of cell wall sporopollenin in Neochloris dissecta (Korshikov) Tsarenko (Chlorococcum dissectum Korshikov) (Chlorophyta) - Strebko, N.P.; Oleksienko, A.A.; Antonenko, S.P.; Komaristaya, V.P.; Комариста, Вікторія Павлівна (Київ : Гідроекологічне товариство України, 2019)
The alga species investigated might be regarded as the potential source of carotenoids, possibly astaxanthin. The alga possesses a relatively high culture growth rate. Further research is necessary on exact species taxonomic attribution, factors of carotenoid accumulation induction, cell carotenoid content HPLC confirmation, and effective methods of carotenoid extraction from the cells with the cell walls containing sporopollenin.
Keywords: Neochloris dissecta; Chlorococcum dissectum; astaxanthin; sporopollenin